Pengaruh Lingkungan Kerja dan Beban Kerja Terhadap Kinerja Pegawai di Lembaga Permasyarakatan (Lapas) Kelas II B Singaraja - Angglelita, Ni Kadek Vina; Dewanti, Made Amanda; Winata, I Gusti Ketut Adi (Ikatan Da'i Indonesia, 2026)
This study aims to analyze the effect of work environment and workload on employee performance at the Class II B Singaraja Correctional Institution. The method used is causal quantitative with multiple linear regression analysis techniques. The population as well as the sample consisted of 73 employees using a saturated sampling technique. Data were collected through questionnaires that had been tested for validity and reliability. The results of the analysis show that partially the work environment has a positive and significant effect on employee performance with a t-value of 2.719 and a significance of 0.008. Workload also has a positive and significant effect on performance with a t-value of 2.782 and a significance of 0.007. Simultaneously, both variables have a significant effect on employee performance with an F-value of 9.440 and a significance of less than 0.05. The coefficient of determination Adjusted R Square of 0.190 indicates that 19% of performance variation can be explained by work environment and workload, while the remaining 81% is influenced by other factors. The regression equation obtained is Y = 8.261 + 0.482X1 + 0.558X2. These findings indicate that although the work environment is not yet optimal and the workload is relatively high, employees are still able to demonstrate good performance. The implication of this study is the importance of improving the quality of the work environment and managing workload proportionally to support better employee performance in the future. This study also provides empirical contributions to human resource management development, particularly in the correctional sector, and serves as a reference for future research